Frontal plane knee mechanics and medial cartilage MR relaxation times in individuals with ACL reconstruction : A pilot study - Kumar, Deepak (2014)
BACKGROUND: The objective of this pilot study was to evaluate cartilage T(1ρ) and T(2) relaxation times and knee mechanics during walking and drop-landing for individuals with anterior cruciate ligament reconstruction (ACL-R). METHODS: Nine patients (6 men and 3 women, Age 35.8±5.4 years, BMI 23.5±2.5 kg/m(2)) participated 1.5±0.8 years after single-bundle two-tunnel ACL reconstruction. Peak knee adduction moment (KAM), flexion moment (KFM), extension moment (KEM), and peak varus were calculated from kinematic and kinetic data obtained during walking and drop-landing tasks. T(1ρ) and T(2) times were calculated for medial femur (MF), and medial tibia (MT) cartilage and compared between subjects with low KAM and high KAM. Biomechanical variables were compared between limbs. RESULTS: The high KAM group had higher T(1ρ) for MT (p = 0.01), central MT (p = 0.05), posterior MF (p = 0.04), posterior MT (p = 0.01); and higher T(2) for MT (p = 0.02), MF (p = 0.05) posterior MF (p = 0.002) and posterior MT (p = 0.01). During walking, ACL-R knees had greater flexion at initial contact (p =0.04), and lower KEM (p = 0.02). During drop-landing, the ACL-R knees had lower KAM (p = 0.03) and KFM (p = 0.002). CONCLUSION: Patients with ACL-R who have higher KAM during walking had elevated MR relaxation times in the medial knee compartments. These data suggest that those individuals who have undergone ACL-R and have higher frontal plane loading, may be at a greater risk of knee osteoarthritis.